2017
DOI: 10.1002/humu.23182
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Rearrangements of Human Amylase Genes Create Multiple Independent CNV Series

Abstract: 19The human amylase gene cluster includes the human salivary (AMY1, MIM# 20 104700) and pancreatic amylase genes (AMY2A, MIM# 104650 and AMY2B, MIM# 21 104660), and is a highly variable and dynamic region of the genome. Copy number 22 variation of AMY1 has been implicated in human dietary adaptation, and in 23 population association with obesity, but neither of these findings has been 24 independently replicated. Despite these functional implications, the structural 25 genomic basis of copy number variation (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In parallel, we obtained independent duplicate copy number measurements by direct analysis of genomic DNA in 1,448 DNA samples from the 1958 Birth Cohort using ratio-based (PRT) methods (17), again demonstrating concordance with previous copy number distributions (Supporting Information Table S1) and the odd-even parity between AMY1 and AMY2A ( Figure 1B). The mean copy numbers found in 1958 Birth Cohort samples were 6.71 (range: 2-15) for AMY1, 2.0 (range: 0-5) for AMY2A, and 2.15 (range: 2-5) for AMY2B.…”
Section: Resultssupporting
confidence: 77%
“…In parallel, we obtained independent duplicate copy number measurements by direct analysis of genomic DNA in 1,448 DNA samples from the 1958 Birth Cohort using ratio-based (PRT) methods (17), again demonstrating concordance with previous copy number distributions (Supporting Information Table S1) and the odd-even parity between AMY1 and AMY2A ( Figure 1B). The mean copy numbers found in 1958 Birth Cohort samples were 6.71 (range: 2-15) for AMY1, 2.0 (range: 0-5) for AMY2A, and 2.15 (range: 2-5) for AMY2B.…”
Section: Resultssupporting
confidence: 77%
“…But if AMY1 CNV does represent an adaptation to increased levels of starch in the human diet, at what point in evolutionary history did it occur, and why did it occur at that time? It has been suggested that it accompanied the development of agriculture [21,22,25,32,46,47], which occurred around 10,000 BC, but it is unlikely that such a major change in the genome could have occurred in such a short space of time. Furthermore, AMY1 CNV has been found in ancient hunter-gatherers, predating the introduction of agriculture [48,49].…”
Section: Evolutionary Drive For Cnv Within Amy1mentioning
confidence: 99%
“…Furthermore, we cannot accurately identify the exact temporal origin of AMY1 CNV, nor when cooking was widely adopted by human ancestors [30]. However, if the origin of AMY1 CNV predates the development of agriculture and postdates the widespread introduction of cooking, and may have been present in the first humans, it does not necessarily mean that it has conferred no selective advantage in modern human history [47]. It is still possible that high numbers of AMY1 copies were favoured in populations with starch-rich diets, and have been retained.…”
Section: Evolutionary Drive For Cnv Within Amy1mentioning
confidence: 99%
“…Copy number variations (CNVs), which include insertions, duplications, and deletions of genomic segments among individuals within species, are currently known to be 50 bps to several Mbps in length (Mills et al, 2011;Iskow et al, 2012;Zarrei et al, 2015). CNVs encompass such more nucleotides than other types of variations (e.g., SNPs and InDels) that they can result in more remarkable effects on the functional gene through perturbing the long-range regulation of gene expression, altering gene dosage or coding sequences, and creating new genes, consequently contributing to phenotypic variations (Redon et al, 2006;Innan and Kondrashov, 2010;Bickhart and Liu, 2014;Shwan et al, 2017). A growing body of evidence shows that CNVs are crucial drivers of phenotypic diversity, evolution, and adaptation in humans and animals (Perry et al, 2008;Iskow et al, 2012;Sudmant et al, 2015;Romero et al, 2017;Rinker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%